The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4236/ce.2018.99095
|View full text |Cite
|
Sign up to set email alerts
|

Change in E-learning Readiness and Challenge for Myanmar Higher Education

Abstract: The advantage of technology has paved way for innovation in higher education. Because of being cost-effective, unlimited time and place, the universities from the developing world are also trying to integrate e-learning into their traditional education system. However, as a fundamental process, they require the readiness assessment before their e-learning implementation. Moreover, the evaluation on readiness should be done as ongoing process so that readiness movements are able to be confirmed, and necessary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Readiness is vital in ensuring the success of education-instruction process and is an important input for learning-teaching system (Bloom, 1995 as cited in Engin, 2017). The and Usagawa (2018) highlighted the necessity of measuring the readiness prior to the implementation of e-learning as it gives awareness to the university of what is required among the students, psychologically and technically. They added that this highlights the degree of preparedness required by a university or organisation of the implementation.…”
Section: Readiness Towards Online Testing Among Studentsmentioning
confidence: 99%
“…Readiness is vital in ensuring the success of education-instruction process and is an important input for learning-teaching system (Bloom, 1995 as cited in Engin, 2017). The and Usagawa (2018) highlighted the necessity of measuring the readiness prior to the implementation of e-learning as it gives awareness to the university of what is required among the students, psychologically and technically. They added that this highlights the degree of preparedness required by a university or organisation of the implementation.…”
Section: Readiness Towards Online Testing Among Studentsmentioning
confidence: 99%
“…According to the ICT development index 2017 released by ITU, Myanmar was one of the countries in ASEAN which had a lower rank of ICT index. Strengthen the claim, The and Usagawa [30] stated that development of ICT in Myanmar educational system has faced various obstacles such as poor telecommunication infrastructure, lack of ICT ability & knowledge, weakness of human resources. Moreover, the statistical data released by UNESCO in 2012 which showed only 5% of Myanmar schools have computer laboratories [31].…”
Section: Myanmarmentioning
confidence: 99%
“…Rohayani et al (2015) further argue the adoption of e-learning should ideally be initiated by measuring the readiness for e-learning. Another study warns that a readiness assessment must be done before elearning is implemented (The & Usagawa, 2018). Adiyarta et al (2018) used the Thirteen-Factor E-Learning Readiness Model in a study and found the "three readiness factors that needed a lot of work" included human resources, technical skills, and content (p. 241).…”
mentioning
confidence: 99%